2000
DOI: 10.1007/s001250051345
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute hyperglycaemia on QTc duration in healthy man

Abstract: A prolonged heart rate-adjusted QT (corrected QT interval: QTc) is a risk factor for sudden death in patients with the long QT syndrome [1], patients with myocardial infarction [2], subjects referred for Holter monitoring [3] and healthy men and women [4±5]. A prolonged QTc interval has been reported in diabetic patients with autonomic neuropathy [6] and is associated with an increased mortality risk in nephropathic Type I (insulin-dependent) diabetic patients [7], as well as with fasting and post-challenge gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
109
2
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 25 publications
6
109
2
4
Order By: Relevance
“…Moreover, intensive insulin treatment during acute myocardial infarction reduces long-term mortality in diabetic patients (9). All this seems consistent with the evidence that an acute increase in plasma glucose levels in normal subjects prolongs the QT interval (10), and that hyperglycemia in acute myocardial infarction can induce such electrophysiological alterations as to favor the occurrence of life-threatening arrhythmias (11).…”
supporting
confidence: 76%
“…Moreover, intensive insulin treatment during acute myocardial infarction reduces long-term mortality in diabetic patients (9). All this seems consistent with the evidence that an acute increase in plasma glucose levels in normal subjects prolongs the QT interval (10), and that hyperglycemia in acute myocardial infarction can induce such electrophysiological alterations as to favor the occurrence of life-threatening arrhythmias (11).…”
supporting
confidence: 76%
“…Gokhroo R. et al (41) showed that, in acute myocardial infarction, an increased plasma glucose level have been demonstrated to be capable of inducing, such electro phsyological alterations as to favour the occurrence of arrhythmias, whose outcome could be fatal. This is consistent with the evidence that, an acute increase in blood glucose level in normal subjects produces a significant QT prolongation (42).…”
Section: Discussionsupporting
confidence: 92%
“…This analysis would suggest that it is chronic hyperglycaemia, rather than the insulin-resistant or hyperlipidaemic aspects of the metabolic syndrome that attenuates autonomic function in Indian Asians. Acute glucose infusion rapidly alters cardiac autonomic function (measured by the QTc on ECG) [30]; in the chronic situation, accumulation of advanced glycation end-products is associated with poorer HRV [31]. In addition, chronic intensive glycaemic control improves cardiac autonomic function [32].…”
Section: Discussionmentioning
confidence: 99%